What Is the Role of HSCT in Philadelphia-Chromosome–Positive and Philadelphia-Chromosome–Like ALL in the Tyrosine Kinase Inhibitor Era? - Vettenranta, Kim; Dobsinska, Veronika; Kertész, Gabriella; Svec, Peter; Buechner, Jochen; Schultz, Kirk R. (Frontiers in Pediatrics, 2022)
Previously, the outcome of paediatric Philadelphia-chromosome–positive (Ph+) ALL with conventional chemotherapy alone was poor, necessitating the use of haematopoietic stem cell transplantation (HSCT) for the best outcomes. The recent addition of tyrosine kinase inhibitors (TKIs) alongside chemotherapy regimens for Ph+ ALL has markedly improved outcomes, replacing the need for HSCT for lower risk patients. An additional poor prognosis group of Philadelphia-chromosome–like (Ph-like) ALL has also been identified. This group also can be targeted by TKIs in combination with chemotherapy, but the role of HSCT in this population is not clear. The impact of novel therapeutic targeted immunotherapies (chimeric antigen receptor T cells and bispecific or drug-conjugated antibodies) has improved the outcome of patients, in combination with chemotherapy, and made the role of HSCT as the optimal curative therapy for Ph+ ALL and Ph-like ALL less clear. The prognosis of patients with Ph+ ALL and persistent minimal residual disease (MRD) at the end of consolidation despite TKI therapy or with additional genetic risk factors remains inferior when HSCT is not used. For such high-risk patients, HSCT using total-body-irradiation–containing conditioning is currently recommended. This review aims to provide an update on the current and future role of HSCT for Ph+/Ph-like ALL and addresses key questions related to the management of these patients, including TKI usage post HSCT, MRD evaluation and related actions post HSCT, the role of HSCT in first complete remission, and the role of HSCT in Ph-like ALL.